2020
DOI: 10.1039/c9lc01212e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid bacterial detection and antibiotic susceptibility testing in whole blood using one-step, high throughput blood digital PCR

Abstract: We report a rapid diagnostic platform that integrates novel one-step blood droplet PCR assay and a high throughput droplet counting system to perform bacterial identification and antibiotic susceptibility profiling directly from whole blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 45 publications
(57 reference statements)
0
68
0
Order By: Relevance
“…48 Abram et al reported a one-step ddPCR assay for rapid detection of multiple antibiotic resistance genes directly from whole blood specimens, which can achieve a sensitivity of 10 CFU mL À1 with a rapid sample-to-answer assay time (1 hour). 50 However, for genotypic ASTs, detailed knowledge of which resistance genes to test is required, which makes the methods not feasible for detecting unknown antibiotic resistant species. Since new forms of resistance evolve quickly, predicting resistance by analyzing a few known resistance genes is not a general solution.…”
Section: Digital Pcr and Digital Lamp For Rapid Astsmentioning
confidence: 99%
“…48 Abram et al reported a one-step ddPCR assay for rapid detection of multiple antibiotic resistance genes directly from whole blood specimens, which can achieve a sensitivity of 10 CFU mL À1 with a rapid sample-to-answer assay time (1 hour). 50 However, for genotypic ASTs, detailed knowledge of which resistance genes to test is required, which makes the methods not feasible for detecting unknown antibiotic resistant species. Since new forms of resistance evolve quickly, predicting resistance by analyzing a few known resistance genes is not a general solution.…”
Section: Digital Pcr and Digital Lamp For Rapid Astsmentioning
confidence: 99%
“…For the processing of monodisperse droplets, the existing microfluidic technologies can be classified into two general categories: (i) On-chip systems, where the droplets remain in the cartridge and analysis and droplet manipulation are performed on-chip [9][10][11][12][13][14][15][16]. (ii) Off-chip systems, where the droplets are transferred into a reaction tube and downstream analysis and/or further manipulation steps are performed in bulk [4,[17][18][19][20]. From an application point of view, devices of the first category offer an ideal method for direct quantification of digital assays but require the use of specialized equipment.…”
Section: Introductionmentioning
confidence: 99%
“…For off-chip solutions, many different droplet generation systems exist [4,[17][18][19][20]. However, most of them are difficult to manufacture, require complex experimental set-ups or need mineral oil for droplet generation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported a technology termed Integrated Comprehensive Droplet Digital Detection (IC 3D), which is capable of analyzing milliliters of droplets within minutes to identify target pathogens ( Figure 1) [23][24][25][26]. Here, we report a phenotypic droplet assay for β-lactamase-mediated antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%